Mycotoxins: Quality Management, Prevention, Metabolism, Toxicity and Biomonitoring - Fokunang, C. N.; Tabi, O. Y.; Ndikum, V. N.; Tembe-Fokunang, E. A.; Kechia, F. A.; Ngameni, B.; Guedje, N.; Jiofack, R. B.; Ngoupayo, J.; Asongalem, E. A.; Torimiro, J. N.; Gonsu, H. K.; et al. (IntechOpen, 2011)
None